Subclinical atherosclerosis and history of cardiovascular events in Italian patients with rheumatoid arthritis: Results from a cross-sectional, multicenter GIRRCS (Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale) study. Issue 42 (October 2017) - Ruscitti, Piero; Margiotta, Domenico Paolo Emanuele; Macaluso, Federica; Iacono, Daniela; D'Onofrio, Francesca; Emmi, Giacomo; Atzeni, Fabiola; Prete, Marcella; Perosa, Federico; Sarzi-Puttini, Piercarlo; Emmi, Lorenzo; Cantatore, Francesco Paolo; et al.
Abstract : Abstract: Several studies have pointed out a significant association between rheumatoid arthritis (RA) and accelerated atherosclerosis. At the best of our knowledge, no such study has been carried out in a large Italian series and, in this study, we aimed to investigate the prevalence of both subclinical atherosclerosis and history of cardiovascular events (CVEs), in patients consecutively admitted from January 1, 2015 to December 31, 2015 to Rheumatology Units throughout the whole Italy. Centers members of GIRRCS ( Gruppo Italiano di Ricerca in Reumatologia Clinica e Sperimentale ) were invited to enrol patients consecutively admitted from January 1, 2015 to December 31, 2015 and satisfying American College of Rheumatology/ European League Against Rheumatism criteria for RA and to investigate each of them for: traditional cardiovascular risk factors: sex, age, smoking habit, total cholesterol, triglycerides, glycaemia, high blood pressure, metabolic syndrome (MS), type 2 diabetes (T2D); RA features: disease duration as assessed from the first symptom, disease activity as evaluated by DAS28, radiographic damage as assessed by hands and feet x-ray, and previous joint surgery; prevalence of both subclinical atherosclerosis and history of CVEs. Eight centers participated to the study. From January 1, 2015 to December 31, 2015, the 1176 patients, who had been investigated for all the items, were enrolled in the study. They were mostly women (80.52%), with a median age of 60 years (range, 18–91 years), a median disease duration of 12 years (range, 0.8–25 years), seropositive in 69.21%. Nineteen percent were in remission; 17.51% presented low disease activity; 39.45% moderate disease activity; 22.61% high disease activity. Eighty-two patients (6.9%) had a history for CVEs (58 myocardial infarction, 38 heart failure, 10 ischemic transitory attack, and 7 stroke). This figure appears to be lower than that reported worldwide (8.5%). After excluding the 82 patients with a history of CV events, subclinical atherosclerosis was detected in 16% of our patients, (176 patients), a figure lower than that reported worldwide (32.7%) and in previous Italian studies. This is the first Italian multicenter study on subclinical and clinical atherosclerosis in patients with RA. We pointed out a low prevalence of both subclinical atherosclerosis and history of CV events. Abstract : Supplemental Digital Content is available in the text